2009
DOI: 10.1111/j.1439-0272.2008.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in varicocele-bearing testes

Abstract: Accelerated apoptosis is a significant factor in the pathophysiology of male infertility disorders associated with abnormal spermatogenesis. This study aimed to investigate apoptosis in varicocele-bearing testes. Sixty four men with varicocele (18 fertile and 46 infertile) were studied compared with eight men with obstructive azoospermic as controls. Apoptosis was assessed in testicular biopsy specimens using terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling (TUNEL) method as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Furthermore, these cells are quiescent and remain in an irreversible G0 stage, and an absence of apoptotic markers has been described (Tay et al, 2007;Hassan et al, 2009;Stiblar-Martincic, 2009) possibly owing to a mechanism that protects them against programmed cell death (Johnson et al, 2008) and explaining our results.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, these cells are quiescent and remain in an irreversible G0 stage, and an absence of apoptotic markers has been described (Tay et al, 2007;Hassan et al, 2009;Stiblar-Martincic, 2009) possibly owing to a mechanism that protects them against programmed cell death (Johnson et al, 2008) and explaining our results.…”
Section: Discussionsupporting
confidence: 69%
“…Because of the importance of adequate spermatogenesis for the integrity of future generations of the species, apoptosis is continuously used as a powerful quality assurance tool to eliminate defective germ cells. Consequently, between 5% and 10% of apoptotic germ cells can normally be observed in histologic studies of testes of young adult men (10,22). Interestingly, uptake of 18 F-ML-10 reflected this physiologic phenomenon.…”
Section: Discussionmentioning
confidence: 94%
“…Ultrastructurally, apoptosis is characterized by cell volume shrinkage, chromatin condensation, blebbing of the nuclear envelope, fragmentation of the nucleus, cytoplasmic vacuolization, condensation of the cytoplasm, and disintegration of the cell into membrane bound remnants termed apoptotic bodies [Kerr et al 1972;Widlak et al 2002;Hassan et al 2009]. Most organelles in the cytoplasm retain their normal appearance only during the early stages of apoptosis, but at later stages cytoplasmic organelles are no longer identifiable [Erkkilä et al 1998].…”
Section: Discussionmentioning
confidence: 99%
“…[Takahashi et al 1996;Stennicke and Salvesen 1997;Wolf et al 1997;Fukamachi et al 1998;Chai et al 1999;Jankowski-Hennig et al 2000;Fanzo et al 2001;Ho and Ames 2002;Ho et al 2003], imbalance of either would lead to the initiation of apoptosis. Abnormally accelerated apoptosis of germ cells may lead to an imbalance of cell proliferation and death resulting in spermatogenic impairment [Hassan et al 2009]. Studies have shown that germ cell degeneration in testes involves an apoptotic mechanism [Billig et al 1995;Henriksen et al 1995].…”
Section: Introductionmentioning
confidence: 99%